Incidencia del régimen simplificado para emprendedores y negocios populares en la recaudación del impuesto a la renta e IVA en la provincia de El Oro durante 2022-2023. - Lopez Barba, Heidy Solange; Maza Vaca, Andrea Nicole (Machala : Universidad Técnica de Machala, 2024)
This study analyzes the impact of the Simplified Regime for Entrepreneurs and Popular Businesses (RIMPE) on the collection of Income Tax (IR) and Value Added Tax (VAT) in the province of El Oro during the years 2022 and 2023, from the perspective of the Internal Revenue Service (SRI). The main objective is to determine if the implementation of RIMPE has had an impact on tax collection and to evaluate its effectiveness as a mechanism to strengthen tax revenues. Under a descriptive and quantitative approach, based on positivist and empirical-analytical paradigms, a documentary analysis of the official SRI data was carried out, complemented with surveys of taxpayers and accountants, as well as interviews with the staff of the FACECOOC project of the Technical University of Machala. The results show that, although the simplified regime sought to facilitate taxation for small businesses, IR collection presented a slight decrease in 2023, which suggests that the RIMPE has not generated significant growth in tax revenue. In contrast, VAT collection showed a moderate increase, which could be linked to a greater formalization of economic activities rather than to a growth in the turnover of taxpayers of the regime. This raises questions about the effectiveness of RIMPE in optimizing tax collection and its real impact on the financial sustainability of the State. A comprehensive review of the regime is recommended, focused on improving its structure, strengthening the tax culture and guaranteeing its effectiveness in generating sustainable income.
El presente estudio analiza el impacto del Régimen Simplificado para Emprendedores y Negocios Populares (RIMPE) en la recaudación del Impuesto sobre la Renta (IR) y el Impuesto al Valor Agregado (IVA) en la provincia de El Oro durante los años 2022 y 2023, desde la perspectiva del Servicio de Rentas Internas (SRI). El objetivo principal es determinar si la implementación del RIMPE ha incidido en la recaudación tributaria y evaluar su efectividad como mecanismo para fortalecer los ingresos fiscales. Bajo un enfoque descriptivo y cuantitativo, basado en paradigmas positivistas y empírico-analíticos, se realizó un análisis documental de los datos oficiales del SRI, complementado con encuestas a contribuyentes y contadores, así como entrevistas con el personal del proyecto FACECOOC de la Universidad Técnica de Machala. Los resultados evidencian que, si bien el régimen simplificado buscaba facilitar la tributación para pequeños negocios, la recaudación del IR presentó una leve disminución en 2023, lo que sugiere que el RIMPE no ha generado un crecimiento significativo en los ingresos fiscales. En contraste, la recaudación del IVA mostró un aumento moderado, lo que podría estar vinculado a una mayor formalización de actividades económicas más que a un crecimiento en la facturación de los contribuyentes del régimen. Esto plantea interrogantes sobre la efectividad del RIMPE en la optimización de la recaudación fiscal y su impacto real en la sostenibilidad financiera del Estado. Se recomienda una revisión integral del régimen, enfocada en mejorar su estructura, fortalecer la cultura tributaria y garantizar su eficacia en la generación de ingresos sostenibles.
Keywords: RIMPE; RECAUDACIÓN TRIBUTARIA; IMPUESTO SOBRE LA RENTA; IVA